THU0364 Rare Erap1 Allotype Combinations Do Not Explain The ERAP1 Association with Ankylosing Spondylitis. (15th July 2016) - Appleton, L.H.; Roberts, A.R.; Vecellio, M.; Wordsworth, B.P.
Abstract : Background: Single nucleotide polymorphisms (SNPs) in ERAP1 are strongly associated with ankylosing spondylitis (AS) (1, 2). ERAP1 is an aminopeptidase involved in the generation of optimal peptide epitopes for presentation by T-cells in the context of major histocompatibility complex (MHC) class I molecules such as HLA-B27. One small study (17 AS cases and 19 controls) suggested that the frequencies of functionally different ERAP1 allotypes differ between patients and controls in AS (3, 4). In this study 13 ERAP1 alleles were identified, many of which were rare and previously unreported; allotype *001 was reported in 44% of cases and 8% controls; allotype *002 in 3% of cases and 45% of controls; allotype *005 in 11% of cases and 29% of controls. The authors also reported that the frequencies of particular allotype combinations differed greatly between AS and controls. For example, the allotype combination *001+*005 was found in 53% of cases, but no controls. This allotype combination (and several other less common combinations) were reported exclusively in AS cases, and were shown in parallel in vitro experiments to be associated with poor processing of peptides and altered HLA class I expression. The results of these unexpected ERAP1 associations clearly required verification in a larger population sample in view of their potentially dramatic implications for understanding one of the most enduring mysteries of the pathogenesis of AS, namely its association with HLA-B27. Objectives: Our study was performed in a much larger sample to assess the veracity of previous suggestions that rare ERAP1 alleles and allotype combinations are associated with AS. Methods: We genotyped 213 AS families and 46 control families using KASP™ technology for 5 SNPs (M349V, K528R, D575N, R725Q, Q730E) to infer ERAP1 allotypes. Allotype and genotype frequencies were compared. Results: Several of the reported rare variants were not observed in our sample. We did not confirm the previously reported ERAP1 associations with rare allotype combinations; the *001 allotype was seen in 17.1% of cases and 23.9% controls. Allotype *002 was seen in 34.7% of cases and 25% controls. The *005 allotype, which was common in the previous report among cases, was not seen in either of our AS cases or controls. The *001+*005 allotype combination, which was observed in 53% of cases in the previous small study was completely absent from both our larger sample of 213 cases and 46 controls. Conclusions: We were unable to confirm the suggested association of AS with rare ERAP1 allotype combinations in this much larger population study. We were also unable to confirm the diversity of ERAP1 haplotypes previously suggested. Further investigation will be required to clarify the correlation of ERAP1 allotype combinations with both functional effects and their potential association with AS. References: Evans DM, et al. Nat Genet 2011;43:761–7. Cortes A, et al. Nat Genet 2013;45:730–40. Reeves E, et al. PNAS 2014;111:17594–9. Reeves E, et al. J Immunol 2013;191:35–43. Disclosure of Interest: None declared